The Effect of Biologic Agents on Steatotic Liver Disease in Patients with Inflammatory Bowel Disease: A Prospective, Open-Label Comparative Trial - Apostolis Papaefthymiou; Styliani Sarrou; Konstantinos Pateras; Ilias D. Vachliotis; Georgios Agrotis; Ioanna-Konstantina Sgantzou; Georgios Perifanos; Andreas Kapsoritakis; Matthaios Speletas; Marianna Vlychou; George N. Dalekos; Spyros Potamianos; et al. (Pharmaceuticals, 2024)
Background: Biologic agents used in patients with inflammatory bowel diseases (IBD) may influence the pathophysiology of coexistent metabolic-dysfunction associated steatotic liver disease (MASLD). This study primarily aimed to evaluate the six-month effect of infliximab or vedolizumab vs. no biologics on presumed hepatic steatosis in patients with IBD. Secondary endpoints were their effect on hepatic fibrosis and parameters related to hepatic metabolism. Methods: This prospective, non-randomized, controlled trial assigned adult bio-naïve patients with IBD into three groups: infliximab, vedolizumab, or controls (receiving no biologic). The baseline was the time of the initiation of biologic agents and the endpoint six months later. Hepatic steatosis was evaluated with transabdominal ultrasonography (Hamaguchi score), whereas controlled attenuation parameter (CAP), fatty liver index (FLI), and hepatic steatosis index (HSI) were used as surrogates. Hepatic fibrosis was evaluated with liver stiffness (LS), fibrosis-4 index (FIB-4), and nonalcoholic fatty liver disease (NAFLD) fibrosis score. Results: Sixty-six patients were assigned to infliximab (n = 26), vedolizumab (n = 14), or control (n = 26); At the endpoint, the Hamaguchi score, CAP, FLI, and HSI were not different between groups. LS was not different between groups; however, FIB-4 was increased within all groups, and NAFLD fibrosis score was increased within infliximab and control groups, without significant biologic × time interactions. Conclusions: No positive or adverse effect of infliximab or vedolizumab vs. no biologic agents was shown on presumed hepatic steatosis in patients with IBD, who have not been previously exposed to biologic agents. Although no effect of both biologic agent on LS, a slight but significant increase in FIB-4 and NAFLD fibrosis score warrants further studying.